2006
DOI: 10.1016/j.cbpa.2006.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the expression of the heat shock protein gene, hsp110, in Xenopus laevis cultured cells and embryos

Abstract: Prokaryotic and eukaryotic organisms respond to various stressors with the production of heat shock proteins (HSPs). HSP110 is a large molecular mass HSP that is constitutively expressed in most adult mammalian tissues. In the present study, we have examined for the first time the expression of the hsp110 gene in Xenopus laevis cultured cells and embryos. The Xenopus hsp110 cDNA encodes an 854 amino acid protein, which shares 74% identity with mice and humans. In Xenopus A6 kidney epithelial cells hsp110 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 125 publications
1
1
0
Order By: Relevance
“…The results of this study indicate that a 24-h Cd-treatment induced a stress response in the skin mediated by an up-regulation of the Hsp70 gene. This is in line with results observed in Xenopus laevis A6 kidney epithelial cells, whereas similar doses of Cd induced expression of several HSPs, including Hsp70 (Gauley and Heikkila, 2006;Woolfson and Heikkila, 2009). Similar to X. laevis cells, the Hsp70 expression in P. bergeri skin was up-regulated only at higher Cd treatment levels (200 and 500 mM) and not at 10 mM.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study indicate that a 24-h Cd-treatment induced a stress response in the skin mediated by an up-regulation of the Hsp70 gene. This is in line with results observed in Xenopus laevis A6 kidney epithelial cells, whereas similar doses of Cd induced expression of several HSPs, including Hsp70 (Gauley and Heikkila, 2006;Woolfson and Heikkila, 2009). Similar to X. laevis cells, the Hsp70 expression in P. bergeri skin was up-regulated only at higher Cd treatment levels (200 and 500 mM) and not at 10 mM.…”
Section: Discussionsupporting
confidence: 92%
“…Current beings induced by low doses of heavy metals and organic pollutants, mainly in aquatic systems and in human diseases [6,[9][10][11][12][13]. For example, Jelaso et al [9] reported that exposure of developing Xenopus laevis tadpoles to low levels of PCB mixture A1254 (5-50 ppb) significantly increased expression of six genes such as p53 nerve growth factor (NGF), proopiomelanocortin, interleukin-1 converting enzyme, ␤-actin and glycerol-dehydes3-phosphate dehydrogenase independent of any health effects.…”
Section: Introductionmentioning
confidence: 99%